Odontological assistance to Down Syndrome patients having congenital heart malformations - Brazoloto, Thiago Medina; Aguiar, Sandra Maria Herondina Coelho Ávila de (ARCHIVES OF HEALTH INVESTIGATION, 2014)
In this study the authors present the frequency and types of congenital heart malformations (CHM) among Down Syndrome (DS) patients emphasizing the prevention of infectious endocarditis (IE) with appropriate antibiotic prophylaxis (ABP). Out of 390 DS patients, 312 (80%) were considered free from any CHM. 78 (20%) presented some CHM; from these 11,54% (n=9) have more than one CHM; ABP to prevent IE was recommended for 41,03% (n=32). Ventricular septal defect was the most frequent CHM (20,51%, n=16). Dentists must know about the patients’ cardiologic diagnosis before a treatment that could cause bleeding, because they have to administer antibiotics to prevent IE. Although some CHM doesn’t need ABP, according to the protocol of the American Heart Association, there are systemic conditions in DS that are relevant to the prescription of antibiotics. Descriptors: Down Syndrome; Heart Defects, Congenital; Endocarditis, Bacterial ; Antibiotic Prophylaxis; Dentistry.